Post-induction allergic reaction in a child with empyema, pulmonary tuberculosis, and a positive direct antiglobulin test: A case report (Indian Journal of Case Reports, 2025)
This case study explores the anesthetic approach for a 3-year-old child diagnosed with left-sided empyema, pulmonary tuberculosis (PTB), and pleural effusion, who also had a positive Direct Antiglobulin Test (DAT). The child was scheduled for thoracotomy with decortication. During the anesthesia induction with fentanyl and propofol, the child developed a widespread maculopapular rash. This reaction was promptly managed with intravenous hydrocortisone and pheniramine. The positive DAT status posed a significant challenge, particularly concerning the planned blood transfusion, leading to the decision to avoid transfusion.